Bilateral cavernous sinus thrombosis secondary to sphenoid sinusitis - Ruano de Pablo, Laura (2020)
Septic cavernous sinus thrombosis is very rare and has only a few published cases. If this pathology is not taken into account, its exploration may be mistaken for an orbital cellulitis and lead to a delay in the initiation of appropriate treatment. The possible morbidity and mortality of cavernous sinus thrombosis is very high, being able to trigger in blindness, hemiparesis or even hypophyseal insufficiency. We present the case of a woman who went to the Emergency Department for presenting headache and fever, and was finally diagnosed with a bilateral cavernous sinus thrombosis due to sphenoid sinusitis, whose agile handling avoided the possible complications that may appear in this entity.